Prediction of Linear Energy Transfer Based on Geant4 Simulation and Neural Networks. Issue 3 (11th January 2023) - Zhang, Xuyan; Chen, Siyu; Liu, Bohang; Cao, Xianfa; Chen, Dongliang; Ma, Lan; Wang, Shulong
Abstract: Most of the traditional studies based on single event effects (SEEs) favor the analysis of electrical mechanisms of semiconductor devices. Professional simulation software in microelectronics requires researchers to have a solid knowledge of microelectronics theory, and the modeling threshold of the software is relatively high, the simulation speed is slow, and accurate simulation of inter‐particle and particle–material interactions is lacking. SEEs are related to linear energy transfer (LET), in this paper, a method is proposed to obtain LET datas to predict SEEs of particles incident on silicon materials by using the Geant4 Monte Carlo toolkit in combination with a dense convolutional network to accurately and rapidly estimate the energy deposition characteristics of the particles. The proposed network structure has a high prediction accuracy with a mean square error （MSE） of only 1.77 × 10 −4 . Compared with Geant4, which takes 1 min to compute a set of data, the proposed network structure takes only 0.0817 s. The method explores the feasibility of using Geant4 to model semiconductor devices combined with deep learning algorithms, providing a new research perspective for the prediction of microelectronic devices and making it possible to explore the influence of integrated circuits by SEEs. Abstract : Combined with the Geant4 Monte Carlo toolkit and dense convolutional networks, the linear energy transfer of particle incident silicon materials is predicted, which shows the feasibility of Geant4 combined with deep learning algorithms to model semiconductor devices, and makes it possible to analyze and explore the impact of single‐event effects on integrated circuits.